Sabbatical Leave Report - Sherman, William M. (2005)
Sabbatical leave report outlining time spent revising the textbook, "Behavior modification", conducting a research project entitled "Motherhood ideology, role balance, and health-promoting behaviors of non-tenured academic mothers with preschool children", and working on course proposals for the Department of Psychology.
Keywords: dept.psy; faculty_collection; sabbatical_report

The predictive validity of the Five-Factor Model of personality with preschool age children: A nine year follow-up study☆ - Abe, Jo Ann A (Journal of Research in Personality, 2005)
This study examined whether maternal ratings of the Five-Factor Model (FFM) obtained when children were 3.5 years would show theoretically coherent patterns of relations with a variety of behavioral referents in the laboratory at 5 years as well as with maternal and self-ratings of psychological functioning in adolescence. As expected, Agreeableness and Conscientiousness were associated with measures of self-regulation at both ages as well as with an internal locus of control, but only Conscientiousness was associated with high academic performance. By contrast, Neuroticism was associated with measures of anxiety and Extraversion was associated with difficulty inhibiting behaviors at both ages. Openness to Experience was associated with sophisticated play behavior at 5 years and self-confidence in adolescence. Overall, this study yielded strong support for the predictive validity of the FFM with preschool age children and provided further evidence that there are striking continuities in personality from early childhood to adolescence. (c) 2004 Elsevier Inc. All rights reserved.
52 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/072-295-048-962-659 tex.type: [object Object]
Keywords: dept.psy; peer-reviewed

Use of visual information in speech perception: evidence for a visual rate effect both with and without a McGurk effect. - Brancazio, Lawrence; Miller, Joanne L (Perception & psychophysics, 2005)
The McGurk effect, where an incongruent visual syllable influences identification of an auditory syllable, does not always occur, suggesting that perceivers sometimes fail to use relevant visual phonetic information. We tested whether another visual phonetic effect, which involves the influence of visual speaking rate on perceived voicing (Green & Miller, 1985), would occur in instances when the McGurk effect does not. In Experiment 1, we established this visual rate effect using auditory and visual stimuli matching in place of articulation, finding a shift in the voicing boundary along an auditory voice-onset-time continuum with fast versus slow visual speech tokens. In Experiment 2, we used auditory and visual stimuli differing in place of articulation and found a shift in the voicing boundary due to visual rate when the McGurk effect occurred and, more critically, when it did not. The latter finding indicates that phonetically relevant visual information is used in speech perception even when the McGurk effect does not occur, suggesting that the incidence of the McGurk effect underestimates the extent of audio-visual integration.
28 citations (Crossref) [2023-10-31] Place: United States Brancazio, Lawrence. Department of Psychology, Southern Connecticut State University, 501 Crescent St., New Haven, CT 06515, USA. brancazioL1@southernct.edu
Keywords: *Speech Perception; *Visual Perception; Adolescent; Adult; Auditory Perception; Cues; Humans; Middle Aged; dept.psy

Effects of reinforcer probability, delay, and response requirements on the choices of rats and pigeons: Possible species differences - Mazur, James E (Journal of the Experimental Analysis of Behavior, 2005)
In Experiment 1 with rats, a left lever press led to a 5-s delay and then a possible reinforcer. A right lever press led to an adjusting delay and then a certain reinforcer. This delay was adjusted over trials to estimate an indifference point, or a delay at which the two alternatives were chosen about equally often. Indifference points increased as the probability of reinforcement for the left lever decreased. In some conditions with a 20% chance of food, a light above the left lever was lit during the 5-s delay on all trials, but in other conditions, the light was only lit on those trials that ended with food. Unlike previous results with pigeons, the presence or absence of the delay light on no-food trials had no effect on the rats' indifference points. In other conditions, the rats showed less preference for the 20% alternative when the time between trials was longer. In Experiment 2 with rats, fixed-interval schedules were used instead of simple delays, and the presence or absence of the fixed-interval requirement on no-food trials had no effect on the indifference points. In Experiment 3 with rats and Experiment 4 with pigeons, the animals chose between a fixed-ratio 8 schedule that led to food on 33% of the trials and an adjusting-ratio schedule with food on 100% of the trials. Surprisingly, the rats showed less preference for the 33% alternative in conditions in which the ratio requirement was omitted on no-food trials. For the pigeons, the presence or absence of the ratio requirement on no-food trials had little effect. The results suggest that there may be differences between rats and pigeons in how they respond in choice situations involving delayed and probabilistic reinforcers.
19 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/053-049-743-382-047 tex.type: [object Object]
Keywords: *Behavior; Animal/ph [Physiology]; *Choice Behavior; *Reaction Time; *Reinforcement; Psychology; Animals; Behavior; Animal; Choice; Choice Behavior; Columbidae; Delay; Fixed interval; Fixed ratio; Key peck; Lever press; Male; Pigeons; Probability; Rats; Rats; Sprague-Dawley; Reaction Time; Reinforcement (Psychology); Species Specificity; Sprague Dawley rat; animal; animal behavior; decision making; dept.psy; male; peer-reviewed; physiology; pigeons and doves; probability; rat; reaction time; reinforcement; review; species difference

Exploring a concurrent-chains paradox: decreasing preference as an initial link is shortened. - Mazur, James E (Journal of experimental psychology. Animal behavior processes, 2005)
Experiments with pigeons and rats on concurrent-chains schedules examined a paradoxical effect reported by R. A. Preston and E. Fantino (1991). One schedule in the concurrent chain had a variable-interval (VI) 60-s initial link, and its terminal link was a 10-s delay to food. The other schedule had an initial link that ranged from VI 60 s to VI 2 s, and its terminal link was a 20-s delay to food. The paradoxical effect–a decrease in preference for the 20-s delay as its initial link was shortened–was found in some conditions but not in others. An analysis of response-reinforcer delays suggested that the paradoxical effect occurred in conditions in which responding on the short VI schedule almost always led to the 20-s delay, eliminating the possibility of switching to the alternative with the shorter delay. Copyright 2005 APA.
1 citations (Crossref) [2023-10-31] Place: United States Mazur, James E. Psychology Department, Southern Connecticut State University, New Haven, CT 06515, USA. mazurj1@southernct.edu
Keywords: *Choice Behavior; *Motivation; *Reinforcement Schedule; Animals; Association Learning; Choice Behavior; Color Perception; Columba; Columbidae; Discrimination Learning; Models; Psychological; Motivation; Psychomotor Performance; Reaction Time; Reinforcement Schedule; animal; article; color vision; decision making; dept.psy; discrimination learning; learning; motivation; pigeons and doves; psychological model; psychomotor performance; reaction time; reinforcement

From Freud to Erikson to Marcia: Concept maps in personality psychology courses - Anthis, K (Teaching of Psychology, 2005)
This study examined concept maps produced by personality psychology students as a function of different types of concept map instruction. The results indicated the number of quantitative items in the students' concept maps significantly increased from the pretest to the posttest, as would be expected over the course of an academic semester. More importantly, the type of instructions the students received at the pretest played a significant role in the number of cross links depicted in the maps at the posttest. I discuss the results in term of the utility of instruction type when using concept maps in social science courses.
tex.unique-id: ISI:000232610800020
Keywords: dept.psy; ⛔ No DOI found

Heuristics and general principles of learning. - Mazur, James E (Behavioural Processes, 2005)
This research on decision-making heuristics is similar to research on animal learning in at least two ways. First, optimality modeling has not proven to be very useful for either research area. Second, both of these research areas seek to find general principles (or heuristics) that are applicable to different species in different settings. However, the basic principles of classical and operant conditioning seem to be more uniform across species and situations, whereas decision-making heuristics can vary for different species and different situations, even for tasks with very similar characteristics.
0 citations (Crossref) [2023-10-31] Place: Netherlands Mazur, James E. Psychology Department, Southern Connecticut State University, New Haven, CT 06515, USA. mazurj1@southernct.edu
Keywords: *Algorithms; *Decision Making; *Learning; *Models; Psychological; Animalia; Animals; Decision-making; Heuristics; Humans; Optimality modeling; behavioral research; conditioned reflex; conference paper; decision making; dept.psy; heuristics; human; instrumental conditioning; learning; mental task; nonhuman